A first-principles high-pressure study of Hf2PX (X=B, C, N). (June 2017) - Li, Hui; Luo, Zhili; Liu, Zhe; Sun, Guodong; Wang, Zhenjun
Abstract: New members of MAX family Hf2 PX (X=B, C, N) were studied by first-principles calculations under pressure range of 0–100 GPa. Their structural, elastic and electronic properties were reported. The results show that they are energetically stable at zero pressure and mechanically stable under pressure range from 0 to 100 GPa. It reveals that Hf2 PB>Hf2 PC>Hf2 PN for the structural parameters of a and V, and Hf2 PB2 PC2 PN for the elastic properties of B, G, E and ν, indicating that Hf2 PN has the best elastic properties and smallest structural parameters among the considered Hf2 PX (X=B, C, N) compounds. Besides, the total and partial DOS shows that the peaks of X–2s states move to lower energy zone with the sequence of X: B→C→N. The present calculations may contribute preliminary results and a better understanding of Hf2 PX for their applications under high pressure environments. Highlights: Structural, elastic and electronic properties of Hf2 PX under pressure are reported. Structural parameters of a and V follow: Hf2 PB>Hf2 PC>Hf2 PN. Elastic properties of B, G, E and ν satisfy: Hf2 PB2 PC>Hf2 PN. DOS shows that the peak of X–2s states moves to lower energy zone following B→C→N.